2019
DOI: 10.1152/ajplung.00356.2018
|View full text |Cite
|
Sign up to set email alerts
|

A novel GABAA receptor ligand MIDD0301 with limited blood-brain barrier penetration relaxes airway smooth muscle ex vivo and in vivo

Abstract: Airway smooth muscle (ASM) cells express GABA A receptors (GABAARs), and previous reports have demonstrated that GABAAR activators relax ASM. However, given the activity of GABAARs in central nervous system inhibitory neurotransmission, concern exists that these activators may lead to undesirable sedation. MIDD0301 is a novel imidazobenzodiazepine and positive allosteric modulator of the GABAAR with limited brain distribution, thus eliminating the potential for sedation. Here, we demonstrate that MIDD0301 rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…5 MIDD0301 has a half-life of almost 4 hours in the lung and only 5% of the circulating amount of MIDD0301 was found in the brain. 14 In sensorimotor studies, no CNS effects were observed at 1000 mg/kg. Importantly, MIDD0301 has excellent anti-inflammatory properties, reducing eosinophil and macrophage numbers in the lungs of asthmatic mice.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…5 MIDD0301 has a half-life of almost 4 hours in the lung and only 5% of the circulating amount of MIDD0301 was found in the brain. 14 In sensorimotor studies, no CNS effects were observed at 1000 mg/kg. Importantly, MIDD0301 has excellent anti-inflammatory properties, reducing eosinophil and macrophage numbers in the lungs of asthmatic mice.…”
Section: Introductionmentioning
confidence: 95%
“…MIDD0301 relaxes constricted ASM and reduces airway hyper‐responsiveness in an ovalbumin‐induced murine model of asthma (MIDD0301 chemical structure and properties are summarized in Figure ) . MIDD0301 has a half‐life of almost 4 hours in the lung and only 5% of the circulating amount of MIDD0301 was found in the brain . In sensorimotor studies, no CNS effects were observed at 1000 mg/kg.…”
Section: Introductionmentioning
confidence: 99%
“…Allosteric GABA A R modulators have been shown to relax ex vivo constricted mouse, guinea pig, and human ASM (Forkuo et al, 2016(Forkuo et al, , 2017(Forkuo et al, , 2018Jahan et al, 2017;Yocum et al, 2019). This prompted investigations with MIDD0301 and MIDD0301S to evaluate enantiomeric differentiation of ASM relaxation.…”
Section: Carboxylic Acid Containing Drugs Are Known To Undergo Glucur...mentioning
confidence: 99%
“…Our group has recently introduced a new class of imidazodiazepines with limited blood–brain barrier (BBB) penetration (Arnold et al, 2018). The lead compound, MIDD0301 bearing a methyl substituent in the (R) configuration, has been shown to relax ex vivo human, guinea pig, and mouse ASM (Forkuo et al, 2018; Yocum et al, 2019), which express discrete GABA A Rs (Gallos et al, 2012). In vivo studies have demonstrated that MIDD0301 alleviates airway hyperresponsiveness (AHR) in several rodent asthma models when delivered orally (Forkuo et al, 2018) and nebulized (Yocum et al, 2019; Zahn et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Other candidates with similar effects on ASM are MIDD0301, an agonist of the A receptor. However, it has the advantage of being almost undetectable in the CNS, without causing sedation ( Figure 7 ; Yocum et al, 2019 ).…”
Section: Gamma-amino Butyric Acidmentioning
confidence: 99%